137k views
1 vote
Please give me an explanation too I need help Solve for y: 2x-y=3

User Emre Isik
by
4.3k points

2 Answers

4 votes

Answer:

y=2x-3

Explanation:

2x-y=3

-2x on both sides of the equal sign which leaves you with -y=-2x+3

divide both sides by negative 1

y=2x-3

User Higginbotham
by
5.2k points
5 votes

Answer:

y = 2x -3

Explanation:

to solve for y, simply isolate the y so in this case move 2x to the right side of the equation in which it becomes -y= -2x +3 and then divide by -1 which is beside the -y essentially cause y cannot be negative so then the equation becomes y = 2x -3

User Elysia
by
4.7k points